(untitled) (World Bulletin of Management and Law, 2023)
The features of the formation of energy prices on a global scale are considered, the factors influencing this process are determined, the trends in the development of the world energy sector are analyzed, the reasons for their appearance are revealed. The article analyzes the forecast for the development of the world energy complex until 2030 by types of energy resources, and also provides an assessment of the state and prospects for the development of energy